Historisitas dalam Filsafat Confucius dan Relevansinya Bagi Kebudayaan Indonesia - Budisutrisna Budisutrisna (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
Confucius philosophy loaded with concepts for cultural improvment. His point of view was focused on the effort to improve uncultured society to be a more cultured society. Confucious had philosophically thought about culture and always relied on its historicity, even though it was implicity. The aim for historicity is to strengthen the unity, intergrity, and cultural harmony.The historicity in Confucius philosophy is directed to his culture philosophy. Based on Confucius thinking about culture, we try to trace to view to the historicity. And then we look for its relevance for National Culture of Indonesia.The material of this research is Confucius philosophy, especially abaout culture and historicity. Philosophical hermeneutic method was used to analyze the data, with its element are: description, historical sustanbility, and reflection.This result of research shows that historicity can be a strong power in cultural. Historicity in Confucius philosophy has relevances for development steps of national culture of Indonesia, which includes: acculturation, education, language, and proggresiviness. Pancasila as essence of Indonesia national culture must become basic for culture system, social system, and physical system.